Tendance actuelle de la consommation des aliments traditionnels dans la ville de Goma, province du Nord-Kivu, à l’est de la République démocratique du Congo - Tchombe, Fidéline Nabintu; Mitima, Honoré Irenge; Mituga, Prudent Ngabe; Mirimba, Bruno Mugisho; Ntabaza, Roger Byumanine; Ombeni, Justin Birashwira; Munyuli, Théodore Mushambanyi (European Scientific Journal, ESJ, 2025)
La nature offre une diversité d’aliments traditionnels. Paradoxalement, l’insécurité alimentaire demeure alarmante dans la ville de Goma. En outre, les études axées sur cette problématique sont d’une rareté inquiétante. Le but de cette étude était d’identifier les types d’aliments traditionnels vendus et consommés en ville de Goma et les facteurs qui en déterminent la consommation. Cette étude avait porté sur un échantillon de 13 producteurs, 52 vendeurs et 126 consommateurs sélectionnés suivant les normes d’échantillonnage aléatoire. Les résultats indiquent que la grande diversité des aliments traditionnels inventoriés était d’origine végétale (55,60%) comparativement à ceux d’origine animale (33,30%) et des champignons (11,10%). A peu près 40,10% des enquêtés incluaient dans leur ration alimentaire au moins un aliment traditionnel 3 fois la semaine. Les aliments traditionnels sont utilisés comme aliment ou comme médicament. Les aliments d’origine animale plus utilisés comprenaient : le miel (90,00%), les peaux de vache ou de chèvre (73,30%), cobaye (52,90%), sauterelles (50,80%), la tope (30,90%) et les chenilles (13,06%). Les aliments d’origine végétales étaient entre autres, les champignons (72,80%), les aubergines sauvages (66,40%), la chayotte (65,40%), les feuilles de colocase (62,80%), la pulpe de courge (58,60%), la morelle noire/verte (55,00%), le tournesol (54,40%), les ignames (50,80%), le gombo (48,10%), la farine de banane (47,60%), les aubergines locales (38,70%). La consommation des aliments traditionnels était trouvée associer à l’existence à domicile des moyens de conservation de ces aliments et au statut coutumier-financier du consommateur (p=0,024., χ2 test). Le taux de consommation ménagère des aliments traditionnels était plus élevé chez les producteurs (cueilleurs/récolteurs) consommaient beaucoup plus les aliments traditionnels que chez les acheteurs-revendeurs (p= 0,011., χ2 test). Comparativement aux taux relevés à hier en Afrique Sub-saharienne, la tendance actuelle de consommation des aliments traditionnels en ville Goma est faible. Des recherches approfondies sont nécessaires à être menées, dans le futur, pour déterminer les implications sanitaires chez les consommateurs avant de commencer les campagnes de sensibilisation sur leurs valeurs nutritionnelles et leur potentiel contribution dans l’amélioration de la qualité du panier de la ménagère. While the nature offers a diversity of traditional food, the current situation of food insecurity is alarming in various homesteads in the Goma city (eastern DR Congo). There are preliminary surveys describing the attachment of the urban community to traditional food items in Goma. The above knowledge gap motivated this survey study. Therefore, the goal of this study survey was to identify the types of traditional food traded/consumed in this town and the drivers (factors) influencing current trend in the consumption of traditional food in urban environment. The study survey was composed of a sample of 13 producers, 52 sellers and 126 consumers who were randomly selected from the entire urban population of consumers/sellers met during interviews. The results indicated that, a variety of traditional food was produced, traded and consumed by local inhabitants from different historical/family background. Most of these traditional food types were of plant origin (55.60%) as compared to animal (33.30%) and fungal (11.10%) origins. About 40.10% of traditional foods were consumed 3 times per week per household. There was a seasonal variability in price of different food types. Consumption behaviors varied according to wealth status and to cultural background. Two categories of traditional food were used as food or medicine. The list of animal-based food types included honey (90.00%), animal skins (73.30%), guinea pig (52.90%), grasshoppers (50.80%), termite (38.70%) and insect caterpillars (13.06%). The list of plant based traditional foods included mushroom (72.80%), wild eggplant (66.40%), leaves of taro (62.80%), gourd pulp and seeds (58.60%), nightshade or green (55.00%), sunflower (54.40%), yams (50.80%), plantain/banana flour (47.60%) and maize/sorghum-based porridges. As compared to producers, the study revealed that consumers/venders had high ability to process/store traditional foods recently collected in the field/nature wild or home-gardens (p=0.024, χ2 test). As compared to sellers/marketers, the key driver of the choice of food items by a given producer/consumer was the consumer’s financial-cultural back ground(statute) (p = 0.011, χ2 test). Aged respondents wanted to shop more food stuffs collected in the wild than from home-gardens. Overall, the level of consumption of traditional food was found to be low in Goma as compared to reports from other urban cities of DR Congo and Sub-Sahara Africa. In future, there is an urgent need for an awareness campaign to be conducted after detailed studies are conducted for the nutritional values, toxicity risks that can be associated to health of consumers of traditional/wild foods. Obviously traditional food types have the potential to contribute in the improvement of the nutritional quality and welfare of consumers of urban and rural households. For producers/collectors/ harvesters, traditional food is likely contributing to the increase of household income, livelihood and wellbeing of users. As nutritional-sensitive products, they have the potential to increase women financial baskets as these are frequently involved in trading traditional foods in Africa.